Experimental Study on Influencing Factors of Aerosol Retention by Pool Scrubbing - Li, Yuxiang; Tong, Lili; Cao, Xuewu (Frontiers in Energy Research, 2021)
During the process of containment depressurization venting, a high-temperature and high-pressure carrier gas with aerosol may be released into the spent fuel pool by a multi-hole injector. This aerosol in the carrier gas can be removed by pool scrubbing. A small-scale pool scrubbing facility was built to study the aerosol pool scrubbing phenomenon using a multi-hole injector. In this study, a gaseous mixture of nitrogen and steam is used to simulate carrier gas, and insoluble solid particles of TiO2 are used to simulate aerosols in the carrier gas. Seven tests were performed to examine the dependence of the decontamination factor (DF) on the pool depth, particle diameter, and steam mass fraction. The results show that log(1 / (1 - Xm)) has a linear relationship with log(DF). DF varies exponentially with pool depth, which has a influence on the retention of aerosols with a larger particle diameter. Particle diameters in the range of 0.2–0.52 μm have little effect on the DF. For low depth pool scrubbing, the steam condensation mechanism is dominant, and the particle diameter does not have a significant effect on the DF. Moreover, the pool scrubbing model is discussed, and an empirical correlation is proposed to evaluate the DF of a pool.